Association of Aortic Stiffness With Biomarkers of Neuroinflammation, Synaptic Dysfunction, and Neurodegeneration. (27th July 2021) - Moore, Elizabeth E.; Liu, Dandan; Li, Judy; Schimmel, Samantha J.; Cambronero, Francis E.; Terry, James G.; Nair, Sangeeta; Pechman, Kimberly R.; Moore, Marissa E.; Bell, Susan P.; Beckman, Joshua A.; Gifford, Katherine A.; et al.
Abstract : Objectives: To test the hypothesis that increased aortic stiffening is associated with greater CSF evidence of core Alzheimer disease pathology (β-amyloid [Aβ], phosphorylated tau [p-tau]), neurodegeneration (total tau [t-tau]), synaptic dysfunction (neurogranin), neuroaxonal injury (neurofilament light [NFL]), and neuroinflammation (YKL-40, soluble triggering receptor expressed on myeloid cells 2 [sTREM2]), we analyzed pulse wave velocity (PWV) data and CSF data among older adults. Methods: Participants free of stroke and dementia from the Vanderbilt Memory and Aging Project, an observational community-based study, underwent cardiac magnetic resonance to assess aortic PWV (meters per second) and lumbar puncture to obtain CSF. Linear regressions related aortic PWV to CSF Aβ, p-tau, t-tau, neurogranin, NFL, YKL-40, and sTREM2 concentrations after adjustment for age, race/ethnicity, education, apolipoprotein (APOE) ε4 status, Framingham Stroke Risk Profile, and cognitive diagnosis. Models were repeated testing PWV interactions with age, diagnosis, APOE ε4, and hypertension on each biomarker. Results: One hundred forty-six participants were examined (age 72 ± 6 years). Aortic PWV interacted with age on p-tau (β = 0.31, p = 0.04), t-tau, (β = 2.67, p = 0.05), neurogranin (β = 0.94, p = 0.04), and sTREM2 (β = 20.4, p = 0.05). Among participants >73 years of age, higher aortic PWV related to higher p-tau (β = 2.4, p = 0.03), t-tau (β = 19.3, p = 0.05), neurogranin (β = 8.4, p = 0.01), and YKL-40 concentrations (β = 7, 880, p = 0.005). Aortic PWV had modest interactions with diagnosis on neurogranin (β = −10.76, p = 0.03) and hypertension status on YKL-40 (β = 18, 020, p < 0.001). Conclusions: Among our oldest participants, ≥74 years of age, greater aortic stiffening is associated with in vivo biomarker evidence of neuroinflammation, tau phosphorylation, synaptic dysfunction, and neurodegeneration, but not amyloidosis. Central arterial stiffening may lead to cumulative cerebral microcirculatory damage and reduced blood flow delivery to tissue, resulting in neuroinflammation and neurodegeneration in more advanced age.